A CONTENT ANALYSIS: THE VISION STATEMENTS OF HIGHER EDUCATION INSTITUTIONS IN INDONESIA - Chit’Jna Amary Kumang; Eeng Ahman (Dinasti Publisher, 2020)
This research is to find out the strategic plan of higher education institutions in Indonesia by analyzing the vision statements of the top 50 higher education institutions in Indonesia according to the Webometrics version in 2018. All vision statements were accessed through the official site of the higher education institutions and then the content analysis, segmentation based on the types of responsible authority (public-private) and the region (Java Island –outside Java Island) were conducted. The analysis of this study was conducted using Voyant Tools, a web-based application for conducting text analysis. The finding of this study was that there were 11 similar keywords used by nearly all higher education institutions. The visions made by the higher education institutions in Indonesia tend to expect quality improvement by targeting a better rank in the national and international scale education level and being future-oriented. It can be seen that 36% of the higher education institutions specifically make several targets in a particular period.